PENINGKATAN PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM (PAI) DENGAN PENERAPAN MODEL PEMBELAJARAN AKTIF COURSE REVIEW HORAY (CRH) - Neni Hasinah (GoAcademica Research dan Publishing, 2022)
The purpose of this classroom action research is to improve the learning achievement of Islamic Religious Education (PAI) students through the CRH active learning model in class IX 7 semester I State Junior High School 6 Bandung in the 2021/2022 school year. This research was conducted from July to September 2021 at State Junior High School 6 Bandung. The subjects of this study were 31 students of class IX 7 as many as 31 students. This Classroom Action Research was conducted in two cycles. Data collection techniques using documentation, observation, and written tests. Data collection tools in the form of observation sheets, test items, and score list documents. Data analysis used comparative descriptive analysis followed by reflection. Each cycle consists of four steps, namely: (1) Planning, (2) Action Implementation, (3) Observation, and (4) Reflection. The results showed an increase in the learning achievement of Islamic Religious Education students, the average value of learning achievement of Islamic Religious Education (PAI) students increased, namely before the action of 69.6, in the first cycle of 77.2 and in the second cycle of 81.9. In addition, the percentage of student learning completeness also increased, namely before the action was 37.5%, the first cycle was 71.9% and the second cycle was 93.8%. So it can be concluded that the CRH active learning model can improve the learning achievement of Islamic Religious Education students in class IX.7 semester I State Junior High School 6 Bandung in the 2021/2022 school year.